Strategi Pembelajaran Inovatif untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Ananda Dilonia; Refa Ayunda Melki; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore innovative learning strategies in fostering students' critical thinking skills. Critical thinking skills are increasingly essential in today’s complex and challenging era. Approaches such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), as well as open discussions and debates, are capable of encouraging students to think analytically, logically, and reflectively. These strategies emphasize the active role of students in the learning process—not merely as recipients of information, but also as seekers and processors of knowledge. Teachers serve as facilitators who create a learning environment that supports exploration and problem-solving. The evaluation of critical thinking skills is conducted through instruments such as rubrics, Higher Order Thinking Skills (HOTS) questions, and analytical essay tests, which allow for an in-depth assessment of students' abilities. The findings show that innovative learning is more effective than conventional methods in developing critical thinking skills. Therefore, these strategies are worth implementing widely in the education system to prepare students to face future challenges critically, creatively, and adaptively.